Design, development, and characterization of an oral push-pull osmotic pump for the controlled release delivery of norfloxacin - Muhammad Abid Mustafa; Zuha Tariq; Obeda Asghar; Umar Ali; Muntaha Gull Shahid; Rabia Zaka; Muhammad Suffyan Butt; Muhammad Junaid Yaqoob (Journal of University Medical & Dental College, 2025)
BACKGROUND & OBJECTIVE:Osmotic pumps are promising methods for controlled drug release. They are devices used for delivering drugs orally or through implantation. The primary aim of this research is to develop a Norfloxacin oral push-pull osmotic pump capable of providing a controlled drug release while ensuring that the release remains unaffected by the hydrodynamics and pH of the surrounding medium.METHODOLOGY:The core tablet was fabricated using direct compression and subsequently coated with HPMC, PEG-400, sorbitol, and acetone as a solvent. Swelling polymers, specifically Guar Gum (Cyamopsis tetragonoloba), Xanthan Gum (polysaccharide B-1459), and Hydroxypropyl Methylcellulose were also included in the fabrication of the core tablet, with NaCl serving as the cosmogenic.RESULTS:The formulations exhibited favorable flow properties. Friability, hardness, and weight variation testing yielded values within limits, indicating satisfactory outcomes. The drug content uniformity ranged from 98.00% to 99.67%, indicating uniform drug distribution within the formulations. Thermal analysis suggested that the sample was thermally stable. Dissolution studies revealed an in vitro dissolution rate of 98.5% over 15 hours. Release kinetics analysis using four models indicated controlled drug release, with the value of regression (R2) confirming this observation and the n exponent suggesting non-Fickian diffusion.CONCLUSION:Osmotic pumps offer zero-order drug delivery, ensuring steady-state drug release to maintain therapeutic levels for a more extended period; thus, they minimize side effects and improve patient compliance.